Evaluating empathy in adolescents with conduct disorders - Kostić, Jelena Slavko; Nešić, Milkica; Stanković, Miodrag; Žikić, Olivera; Marković, Jasminka (Vojnosanitetski pregled, 2017)
Background/Aim. According to currently available data, there is no research dealing with evaluating empathy in adolescents with conduct disorders in our region. The aim of the research was to examine the differences in the severity of cognitive and affective empathy in adolescents with and with no conduct disorder, as well as to examine the relationship between cognitive and affective empathy and the level of externalization in adolescents with conduct disorder. Methods. This research was conducted on 171 adolescents, aged 15 to 18, using the Interpersonal Reactivity Index, Youth Self-Report and a Questionnaire constructed for the purpose of this research. Results. The results showed that adolescents with conduct disorder had significantly lower scores for Perspective Taking (t = 3.255, p = 0.001), Fantasy (t = 2.133, p = 0.034) and Empathic Concern (t = 2.479, p = 0.014) compared to the adolescents in the control group, while the values for Personal Distress (t = 1.818, p = 0.071) were higher compared to the control group, but the difference was not statistically significant. The study showed a statistically significant negative correlation between Perspective Taking and aggression (r = -0.318, p = 0.003) and a negative correlation between Perspective Taking and the overall level of externalizing problems (r = -0.310, p = 0.004) in the group of adolescents with conduct disorder. Conclusion. This research contributes to better understanding of behavioral disorders in terms of individual factors, especially empathic reactivity. Preventive work with young people who have behavioral problems associated with empathy deficit disorder proved to be an important tool in preventing the development, or at least relieving the symptoms, of this ever more common disorder.